1967
DOI: 10.1103/physrevlett.18.385
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Energy of Positrons in Metals

Abstract: This Letter reports an important new discovery in positron annihilation in metals, viz., that positrons are not always thermalized before annihilation and thus that the ultimate resolution of the technique is limited. The next paragraphs outline the experimental and theoretical discoveries of this phenomenon, and present the results of calculation and measurements.Observations of positron motions in metals, first reported last year, 1 ' 2 have been continued in a series of metals over a wider range of temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Angular-correlation apparatus capable of achieving a resolution comparable with the thermal motion of positrons at liquid-helium temperature was recently built by us 6 and hence we attempted to resolve the discrepancy between the most recent theoretical predictions 5 and previous measurements. 1 In a series of carefully annealed metals of widely different valence-electron densities (K, Mg, and Al) we have observed that positrons are close to thermal equilibrium with the sample at liquid-helium temperature. Assuming that the best fit to the total smearing of the angular-correlation curve reflects just the optical resolution, positron penetration into the sample, and the Maxwell-Bo ltzmann momentum distribution of free positrons at temperature T, we find T = 25 ± 25°K in K, T=10±10°KinMg, and T = 30± 25°K in Al.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Angular-correlation apparatus capable of achieving a resolution comparable with the thermal motion of positrons at liquid-helium temperature was recently built by us 6 and hence we attempted to resolve the discrepancy between the most recent theoretical predictions 5 and previous measurements. 1 In a series of carefully annealed metals of widely different valence-electron densities (K, Mg, and Al) we have observed that positrons are close to thermal equilibrium with the sample at liquid-helium temperature. Assuming that the best fit to the total smearing of the angular-correlation curve reflects just the optical resolution, positron penetration into the sample, and the Maxwell-Bo ltzmann momentum distribution of free positrons at temperature T, we find T = 25 ± 25°K in K, T=10±10°KinMg, and T = 30± 25°K in Al.…”
mentioning
confidence: 97%
“…The CPA starts to break down for nonresonant inelastic processes where the energy transfered is a large fraction of the kinetic energy in one of the channels. 1 Consequently, a comparison can be made with a simple model like the following: W 119 W 00 =<*> for x< 0, W 00 = 0 and W u = 1 for x> 0, and W 01 = V (a constant) for 0 < x^ A and W 01 = 0 for x>A.…”
mentioning
confidence: 99%
“…measurement It should be noted that the problem of positron effective mass was considered in a number of theoretical (14 to16) and experimental(17,18) works and the positron effective mass value M*in Na and Rb was measured equal to 2 M where M i s the free positron mass. Recent detailed calculation(16) showed that in metals M*/M the previously obtained experimental values.…”
mentioning
confidence: 99%
“…Positron thermalization in solids at low temperatures is an interesting and challenging problem that has been studied both experimentally and theoretically every now and then over the last 40 years. [1][2][3][4][5][6][7] Besides from the point of view of positron-host interactions, the problem is important also when considering positron annihilation studies of defects in solids. In analyzing the annihilation radiation data, it is generally assumed that the positron is in thermal equilibrium ͑or very near͒ with the host very soon after implantation ͑within 10 ps͒ even at 10 K. This assumption is widely accepted to be true irrespective of the material.…”
Section: Introductionmentioning
confidence: 99%